Effect of iron doping on the hydrophobicity of titanium dioxide film: experiment and simulation. (17th July 2020) - Wei, Hengbin; Feng, Jiaheng; Ma, Chuandong; Li, Zhihao; He, Meng; Wang, Junxiang; You, Xiaofang; Li, Lin
Abstract : In this study, we carried out experiments and molecular dynamics simulations to identify the effect of Fe doping on the hydrophobicity of a titanium dioxide film. TiO2 and Fe-doped TiO2 films were fabricated in situ by atomic layer deposition without annealing. X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were used to characterise the crystal structure and elemental composition. Iron doping resulted in the TiO2 becoming more hydrophobic at a macroscopic level, as estimated by atomic force microscopy observations and static contact angle measurements. Furthermore, the effect of iron doping on the structure and kinetics of water molecules on the exterior of TiO2 were studied by molecular dynamics simulations. On the basis of the XPS results, the Fe-TiO2 surface matrix has a Ti:Fe ratio of 36:5. In addition, the density distribution of oxygen and hydrogen atoms indicate that interfacial water molecules enter the Fe-TiO2 film more easily and hydrogen atoms in the water molecules are oriented upward at the interface. The self-diffusion coefficients indicate that iron doping makes the TiO2 more hydrophobic, which is consistent with the macroscopic test results. GRAPHICAL ABSTRACT: